Transforming the legislative: a pending task of Brazilian and Colombian constitutionalism - García-Jaramillo, Santiago; Valdivieso-León, Camilo (Revista de Investigações Constitucionais, 2018)
The Constitutions of 1988 in Brazil and 1991 in Colombia have instantiated a complex process of transformative constitutionalism associated with the protection of rights, and the inclusion of minority groups. In spite of the prominent role of the judiciary in these processes, it should be stated that these Constitutions recognized the importance of the legislative branch within the transformations they seek to achieve. The question that remains open is whether a strong intervention by the judiciary is instrumental to put the legislature back in shape and put it in tune with the transformation that both Constitutions seek to achieve. As this paper will show, despite the good decisions delivered when deciding particular cases, overall, transformative constitutionalism based on the prominent role of the Courts has not been that transformative in terms of reforming political institutions. In this sense, what this paper seeks to highlight is that, in order to develop an adequate theory on judicial review, it is crucial to truly identify the limitations of constitutionalism and what judicial review can and cannot do.